Entrepreneurial Skills and Youth Employment in Kogi State, Nigeria: The Case of N-Power - Enimola, Dare Joseph; Orugun, Juwon Johnson; Nafiu, Akeem Tunde (Journal of Asian Business Strategy, 2019)
This study aimed at investagiting the effects of entrepreneurial skills on youth employment in Kogi State, using N-Power as a case study. Survey research design was adopted. The study adopted snowball sampling technique to select N-Power beneficiaries. A well-designed questionnaire was used as a viable instrument to collect data from beneficiaries in N-Teach, N-Health, N-Tax and N-Agro. Data collected were analysed using Multiple Regression and Ordered Probit Regression Model. Finding shows that entrepreneurial skills development has significant effect on N-Power beneficiaries in Kogi State. Finding furthers shows that interpersonal relation skill, technology adoption skill, decision-making skill and risk-taking skill have significant and positive relationship with youth self-employment in Kogi State. The study concluded that the acquisition of entrepreneurial skills is a vital approach towards self-employment. The study recommended that the government and policy-makers should device special focus for interpersonal relation skill, decision-making skill, technology adoption skill and risk-taking skill of N-Power beneficiaries; with less attention to financial literacy and creative thinking skills.